Recurrence of hyperprolactinaemia following discontinuation of dopamine agonist therapy in patients with prolactinoma occurs commonly especially in macroprolactinoma. - Barber, T; Kenkre, J; Garnett, C; Scott, R; Byrne, J; Wass, J (2011)
CONTEXT: The optimal duration of dopamine agonist (DA) therapy in prolactinoma is unknown. There are concerns that despite low recurrence rates in highly selected groups, high recurrence rates after DA withdrawal may occur in routine practice. OBJECTIVE: To explore recurrence of hyperprolactinaemia and predictive factors following DA withdrawal in patients with microprolactinoma and macroprolactinoma. DESIGN: A retrospective study on adult patients with confirmed prolactinoma attending the Oxford Endocrine Department. PATIENTS AND MEASUREMENTS: We identified patients with macroprolactinoma (n = 15) and microprolactinoma (n = 45) treated with DA therapy for >3 years, with a trial off DA therapy. None had other treatments. Measurements included recurrence of hyperprolactinaemia following DA withdrawal, tumour size (macroprolactinomas), duration of DA therapy, prolactin levels (baseline, during DA therapy, recurrence) and time to recurrence. Data were reported as mean (range). RESULTS: During DA therapy, prolactin levels suppressed to normal range in all patients with macroprolactinoma and microprolactinoma, and most macroprolactinomas (n = 14) had substantial tumour shrinkage. Hyperprolactinaemia recurred in 93% of macroprolactinomas (n = 14) at 8·8 months (3-36) and 64% of microprolactinomas (n = 29) at 4·8 months (3-12). Duration of DA therapy was 7·5 years (4-15) for macroprolactinomas and 4·1 years (3-10) for microprolactinomas. Prolactin levels during DA therapy were 144 mU/l (7-336) for macroprolactinomas and 278 mU/l (30-629) for microprolactinomas. For microprolactinomas, prolactin levels during DA therapy were less suppressed in those with recurrence than in those without recurrence (P < 0·05). CONCLUSIONS: In routine practice, hyperprolactinaemia recurs early in most macroprolactinomas (93%) and microprolactinomas (64%) following DA therapy discontinuation. For most macroprolactinomas, cessation of DA cannot be recommended even after 7 years of therapy.